A tv mais feliz do brasil: a proposta de interação do SBT com a audiência - Rafael Barbosa Fialho Martins (2016)
This research discusses the proposal of interaction that the TV Station called Sistema Brasileiro de Televisão (SBT) sets front of his audience, which spontaneously is known for manifestations of affection and passion for the channel in social networks. In the above situation, one aspect is sometimes quoted, but little depth: the formal scope of television, which we consider a key aspect of the relationship hereby established with the audience. Thus, it aims to highlight the SBT style contribution to the interaction with the public. As empirical object, chose institutional vignettes. Our research problem investigates how vignettes SBT express a style which proposes and gives see the kind of interaction that establishes the channel with your audience. For the analysis, we use the methodological approach of the television style trying to understand how things like sound, image and text are part and include the cultural context in which they operate. We conclude that the interaction in question is supported by the mediation of Brazilianness, family, Silvio Santos and feelings, which mark a relationship based on proximity. The aesthetic level, we highlight the following stylistic elements: the set design and performance of the actors help figuring Brazil and the family intended by SBT, editing marks the place of superiority of the channel owner, and the soundtrack and mounting contribute to aesthetically translate the feelings evoked by watching the station. We can identify some brands of a SBT Style: warm colors, effusive activity of the issuer artists, lively soundtrack, including film archive of images and programs, redundancy between image and sound, didacticism etc. Due to the proximity with which the broadcaster invites the viewer, we believe introducing up an "electronic audience" that promotes interaction with the SBT that runs between the projection and identification with fuel as our emotions and feelings.